Предмет: Алгебра,
автор: Athlete1111
1) (3x-1)(2x-3)=(6x-5)(x-2) +4
2) 3(x-1)(x+1) - 5 =(3x+2)(x-1)
Ответы
Автор ответа:
0
1)6х^2-9х-2х+3=6х^2-12х-5х+10+4
6х-11=0
Х=11/6
2)3(х^2+х-1-х)-5=3х^2-3х+2х-2
3х^2+3х-3-3х-5-3х^2+3х-2х+2=0
-х-5=0
Х=-5
6х-11=0
Х=11/6
2)3(х^2+х-1-х)-5=3х^2-3х+2х-2
3х^2+3х-3-3х-5-3х^2+3х-2х+2=0
-х-5=0
Х=-5
Похожие вопросы
Предмет: Алгебра,
автор: segedenkouli
Предмет: Биология,
автор: armen8300
Предмет: Алгебра,
автор: knazmaks60
Предмет: Химия,
автор: gamsims
Предмет: Математика,
автор: Minelove